Invasi dan Tingkat Serangan Ulat Bawang (Spodoptera exigua Hubner) pada Dua Kultivar Tanaman Bawang Merah di Desa Songan, Kecamatan Kintamani, Kabupaten Bangli - MARSADI, DICKY; SUPARTHA, I WAYAN; SUNARI, A.A.A.A. SRI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.4, Oktober 2017, 2017)
Invasion and Attack level of Beet Armyworm (Spodoptera exigua Hubner) on Two Cultivars of Onion in Songan Village, Kintamani, Regency of Bangli This study was aims to determine the invasion and attack level of beet armyworm (S. exigua) on two cultivars of onion. The study was conducted 940 m above sea level at Songan Village, Kintamani, Regency of Bangli from December 2016 to February 2017. This study implemented surveying method by taking 10 samples plant per plot with 5 replications. Sampling was conducted by using U-sistematics patern. The results showed that the invasion occurred during the onion crop was 7 days after planting (dap) and experienced a peak in old plants 17 dap. There was difference larvae of S. exigua population on both varieties of onion crop from the initial observation until the end of the observation. The highest larval populations present in Batu Ijo variety in the amount of 2.4 larvae per clump while variety of Bima Brebes was 1.3 larvae per clump. The attacking level of Bima Brebes variety was 4,86% lower compared on Batu Ijo which is 9,95%. Both onion varieties show difference in productions where Batu Ijo variety has 112,2 grams per clump while Bima Brebes 125,8 grams per clump.